Can innovations in traditional pork products help thriving EU untapped pig breeds? A non-hypothetical discrete choice experiment with hedonic evaluation. (August 2019) - Kallas, Z.; Varela, E.; Čandek-Potokar, M.; Pugliese, C.; Cerjak, M.; Tomažin, U.; Karolyi, D.; Aquilani, C.; Vitale, M.; Gil, J.M.
Abstract: The EU is supporting measures that stimulate enhanced value-added products in order to conserve local and threatened livestock breeds. Several Traditional Pork Products (TPP) and Innovative Traditional Pork Products (ITPP) with health innovations from four untapped pig breeds in Spain ( Porc Negre Mallorquí ), Croatia ( Turopolje ), Italy ( Cinta Senese ) and Slovenia ( Krškopolje ) were analysed. Consumers' "Non-hypothetical" willingness to pay (WTP) and hedonic evaluation were investigated. An integrated experimental approach using two Non-Hypothetical Discrete Choice Experiment (NH-DCE) was carried out before and after a hedonic evaluation test. Results showed that the health innovative products (ITPP) received similar and even lower WTP than the "control" products (TPP) from the untapped pig breeds. The TPP outperformed products enriched with healthy ingredients or with reduced undesirable compounds. The potential demand for traditional and "unaltered" product from the rustic pig breeds could contribute to their conservation. A market niche exists, where consumers appreciate these high-quality products and where no "add-ons" are required to enhance their uptake. Highlights: Traditional pork products may help thriving the untapped and threatened EU pig breeds. Innovative pork products from local breeds do not outperform the traditional ones. Consumers appreciate the pork products from local breeds with no healthy "add-ons". Non-hypothetical choice scenarios revealed potential demand for traditional pig products. Preferences patterns are built on consumer's health beliefs and their hedonic evaluation.